Realistic mathematics education and junior high school students' mathematical reasoning, communication, and self-efficacy: A quasi-experimental study - Amrullah Amrullah; Jarnawi Afgani Dahlan; Endang Wahyuningrum (Panicgogy International Journal, 2026)
Mathematical reasoning, mathematical communication, and self-efficacy are three interrelated competencies in mathematics learning, yet they are frequently neglected in conventional instruction that emphasizes rote procedural memorization. This study examined the effect of the Realistic Mathematics Education (RME) approach on eighth-grade students’ mathematical reasoning ability, mathematical communication ability, and self-efficacy on the topic of circles. A quantitative approach with a nonequivalent control group quasi-experimental design was employed, involving 25 students in an experimental group who received RME-based instruction and 24 students in a control group who received conventional instruction, selected through purposive sampling at a private junior high school in Batam, Indonesia. Data were collected using essay-type tests of reasoning and communication ability together with a Likert-scale self-efficacy questionnaire, and were analyzed using one-sample and independent-samples t-tests after normality and homogeneity assumptions were confirmed. The results showed that the RME approach did not produce a statistically significant effect on mathematical reasoning ability (p = 0.419), but produced a significant effect on mathematical communication ability (p = 0.028) and self-efficacy (p = 0.002) compared with conventional instruction. These findings suggest that students’ engagement in contextual problems, group discussion, and presentation of solutions within the RME stages was more effective in fostering the ability to communicate mathematical ideas and self-confidence than in advancing formal reasoning within a relatively short intervention period. This study contributes to the RME literature by demonstrating that the effectiveness of an instructional approach is multidimensional and uneven across mathematical competencies, implying that teachers need to design additional reinforcement for reasoning when implementing RME over a short duration.